1999
DOI: 10.1083/jcb.144.5.1019
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase-PEST Regulates Focal Adhesion Disassembly, Migration, and Cytokinesis in Fibroblasts

Abstract: In this article, we show that, in transfected COS-1 cells, protein tyrosine phosphatase (PTP)-PEST translocates to the membrane periphery following stimulation by the extracellular matrix protein fibronectin. When plated on fibronectin, PTP-PEST (−/−) fibroblasts display a strong defect in motility. 3 h after plating on fibronectin, the number and size of vinculin containing focal adhesions were greatly increased in the homozygous PTP-PEST mutant cells as compared with heterozygous cells. This phenomenon appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
217
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(236 citation statements)
references
References 60 publications
(119 reference statements)
15
217
2
2
Order By: Relevance
“…:http://dx.doi.org/10.7314/APJCP.2013.14.1.287 Low PTPN12 is Associated with Poor Prognosis in Operable Triple-negative Breast Cancer PTPN12 is also thought to play an important role in cell adhesion and motility, and is involved in cancer metastasis (Andersen et al, 2004;Streit et al, 2006;Hunter, 2009;Kwong et al, 2009;DeSantis et al, 2011;Rhee et al, 2012). To date, several researches reported that some oncogenes and cell adhesion molecules such like c-ABL, p130 (Cas), CAKbeta, and PSTPIP1 were associated with PTP family (Angers-Loustau et al, 1999;Andersen et al, 2004;Westbrook et al, 2008). Tingting Sun et al reported that PTPN12 suppressed transformation by interacting with and inhibiting tyrosine kinase signaling, such as EGFR and HER2.…”
Section: Discussionmentioning
confidence: 99%
“…:http://dx.doi.org/10.7314/APJCP.2013.14.1.287 Low PTPN12 is Associated with Poor Prognosis in Operable Triple-negative Breast Cancer PTPN12 is also thought to play an important role in cell adhesion and motility, and is involved in cancer metastasis (Andersen et al, 2004;Streit et al, 2006;Hunter, 2009;Kwong et al, 2009;DeSantis et al, 2011;Rhee et al, 2012). To date, several researches reported that some oncogenes and cell adhesion molecules such like c-ABL, p130 (Cas), CAKbeta, and PSTPIP1 were associated with PTP family (Angers-Loustau et al, 1999;Andersen et al, 2004;Westbrook et al, 2008). Tingting Sun et al reported that PTPN12 suppressed transformation by interacting with and inhibiting tyrosine kinase signaling, such as EGFR and HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of tyrosine phosphorylation of FAK, paxillin and p130Cas in Tpr-Met transformed cells may re¯ect a decrease in b1 integrin levels observed in TprMet transformed cells (data not shown) and the accompanying decrease in integrin dependent focal adhesions. Alternatively, since several phosphatases are involved in the dephosphorylation of FAK and associated focal adhesion proteins (Angers-Loustau et al, 1999;Yu et al, 1998), decreased tyrosine phosphorylation of focal adhesion proteins may re¯ect enhanced phosphatase activity. However, treatment of Tpr-Met transformed ®broblasts with tyrosine phosphatase inhibitors such as pervanadate or peroxovanadium failed to promote cell spreading (data not shown) and FAK tyrosine phosphorylation in pervanadate treated Tpr-Met transformed cells was signi®cantly reduced when compared with control Fr3T3 ®broblasts (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and enzymatically-inactive mutant (C231S) of mouse PTP-PEST were cloned into the expression vectors pEF-BOS and pcDNA3.1 (Angers-Loustau et al, 1999). Human LYP, PTPH1, SHP1, LMPTP-B and HePTP cDNA in mammalian expression vector pEF5HA were described previously (Bottini et al, 2002;Brockdorff et al, 1999;Gjörloff-Wingren et al, 2000;Saxena et al, 1998;Vang et al, 2005).…”
Section: Expression Plasmidsmentioning
confidence: 99%
“…In non-lymphoid cells, PTP-PEST participates in the dynamic regulation of focal adhesions, integrin signaling, and Rac-dependent motility (Angers-Loustau et al, 1999;Sastry et al, 2002). In B cells, PTP-PEST, was reported to reduce the phosphorylation of Shc, Pyk2, Fak, and Cas, and to inhibit activation of the Ras pathway (Davidson and Veillette, 2001).…”
Section: Introductionmentioning
confidence: 99%